Pengaruh Gaya Kepemimpinan Partisipatif dan Transaksional terhadap Kinerja Karyawan melalui Motivasi Kerja industri FnB Sekitar Jawa Barat - Moch. Azriel Alvirezhy; Jihan Fadhilah Febriana; Singgih Saputra (Journal of Innovative and Creativity, 2026)
Employee performance is an important factor in determining the success of the organization, especially in the food and beverage industry which demands effective work and quality service. This study was conducted to see how participatory leadership and transactional leadership influence employee performance, with motivation to work as intermediaries, in the food and beverage industry in West Java Province. Data was collected through surveys using structured questionnaires distributed to FnB industry employees using a non-probability sampling method. The data obtained were then analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, accompanied by validity and reliability testing. The results show that participatory leadership and transactional leadership both have a positive and significant effect on employee performance. In addition, work motivation has been proven to play a role as a liaison that strengthens the influence of these two leadership styles on employee performance.